Quantity and Quality Analysis and Management of Dental Solid Waste Produced in Private Office in Urmia - Nasrollahi, Mohtaram; Zazouli, Mohammad-Ali; Balarak, Davoud; Moradi Golrokhi, Mojtaba (Journal of Dental School, 2019)
Objective: Dental solid wastes often contain hazardous substances. The first step of management of dental solid wastes includes detection and classification of these substances. This study aimed to qualitatively and quantitatively assess the management of solid wastes by dental offices in Urmia city in 2013. Methods: This descriptive study was conducted on all private dental offices in Urmia city and six samples were collected of the wastes of each office per season. Samples were manually searched, divided into 16 different categories and weighed by a digital scale. In the next step, the weighed components were classified according to their characteristics and hazardous potential. Results: The total amount of solid wastes produced by dental offices in Urmia city was 81 kg/day consisting of 28.3% infectious wastes, 59% domestic-like wastes, 9.6% chemical and pharmaceutical wastes and 2.7% toxic wastes. Waste reduction and recycling programs were not performed in any office. Conclusion: Considering the type and quantity of generated dental solid wastes, especially the infectious wastes and their adverse effects on public health and the environment, a specific strategy must be designed for management of dental solid wastes.